Dissociation in control of physiological and behavioral responses to emotional stress by cholinergic neurotransmission in the bed nucleus of the stria terminalis in rats - Gouveia, Marianna K. [UNESP]; Miguel, Tarciso T.; Busnardo, Cristiane; Scopinho, Amï¿½rica A.; Corrï¿½a, Fernando M.A.; Nunes-De-Souza, Ricardo L. [UNESP]; Crestani, Carlos C. [UNESP] (Elsevier, 2016)
The bed nucleus of the stria terminalis (BNST) is a forebrain structure implicated in physiological and behavioral responses to emotional stress. However, the local neurochemical mechanisms mediating the BNST control of stress responses are not fully known. Here, we investigated the involvement of BNST cholinergic neurotransmission, acting via muscarinic receptors, in cardiovascular (increase in blood pressure and heart rate and fall in tail skin temperature) and neuroendocrine (increase in plasma corticosterone) responses and behavioral consequences (anxiogenic-like effect in the elevated plus-maze) evoked by acute restraint stress in rats. Bilateral microinjection into the BNST of either the choline uptake inhibitor hemicholinium-3 (3 nmol/100 nl) or the muscarinic receptor antagonist methylatropine (3 nmol/100 nl) enhanced the heart rate increase and inhibited the anxiogenic-like effect observed in the elevated plus-maze evoked by restraint. However, neither hemicholinium-3 nor methylatropine affected the increase in blood pressure and plasma corticosterone levels and the fall in tail skin temperature. Facilitation of local cholinergic signaling by microinjection of the acetylcholinesterase inhibitor neostigmine (0.1 nmol/100 nl) into the BNST reduced restraint-evoked pressor and tachycardiac responses and the fall in tail cutaneous temperature, without affecting the increase in plasma corticosterone. All effects of neostigmine were completely abolished by local BNST pretreatment with methylatropine. These findings indicate an opposite role of BNST cholinergic neurotransmission, acting via local muscarinic receptor, in control of cardiovascular responses (inhibitory influence) and emotional consequences (facilitatory influence) evoked by restraint stress. Furthermore, present findings provide evidence that BNST control of neuroendocrine responses to stress is mediated by mechanisms others than local cholinergic signaling.
Keywords: Anxiety; BNST; Cardiovascular; Corticosterone; Elevated plus maze; Extended amygdala; Muscarinic receptors